Liquid chromatography for multimycotoxin detection for filamentous fungi identification - Soares, Célia (2010)
Mycotoxins are secondary metabolites produced by specific filamentous fungi. Among the most relevant mycotoxigenic producer fungi are some Aspergillus species such as the ones belonging to the Aspergillus section Flavi. These are known to produce the highly carcinogenic aflatoxins (AFB1, AFB2; AFG1 and AFG2) and cyclopiazonic acid (CPA) in agricultural commodities. Besides the issues related to food safety, aflatoxins and CPA analysis can also be routinely used for identification purposes within the Aspergillus section Flavi, since the various species exhibit different mycotoxin profiles. Aflatoxins are mainly produced by some strains of Aspergillus flavus and Aspergillus nomius and by all strains of Aspergillus parasiticus, whereas CPA is mainly produced by Aspergillus flavus strains. The aim of this study was to develop a rapid HPLC method that could detect simultaneously both these mycotoxins. For this purpose twenty two strains belonging to Aspergillus section Flavi were tested for aflatoxins and CPA production. Extracts were analysed using a HPLC system. The tested methodology allowed the separation of CPA from AFGs and AFBs in a HPLC single run and proved to be a useful tool for helping in the identification of the strains in study. Data from these assays will be presented and discussed.